One-Atom Substitution Enables Direct and Continuous Monitoring of Histone Deacylase Activity - Zessin, Matthes; Kutil, Zsófia; Meleshin, Marat; Nováková, Zora; Ghazy, Ehab; Kalbas, Diana; Marek, Martin; Romier, Christophe; Sippl, Wolfgang; Bařinka, Cyril; Schutkowski, Mike (Biochemistry (Easton), 2019)
We developed a one-step direct assay for the determination of histone deacylase (HDAC) activity by substituting the carbonyl oxygen of the acyl moiety with sulfur, resulting in thioacylated lysine side chains. This modification is recognized by class I HDACs with different efficiencies ranging from not accepted for HDAC1 to kinetic constants similar to that of the parent oxo substrate for HDAC8. Class II HDACs can hydrolyze thioacylated substrates with approximately 5-10-fold reduced kcat values, which resembles the effect of thioamide substitution in metallo-protease substrates. Class IV HDAC11 accepts thiomyristoyl modification less efficiently with an ∼5-fold reduced specificity constant. On the basis of the unique spectroscopic properties of thioamide bonds (strong absorption in spectral range of 260-280 nm and efficient fluorescence quenching), HDAC-mediated cleavage of thioamides could be followed by ultraviolet-visible and fluorescence spectroscopy in a continuous manner. The HDAC activity assay is compatible with microtiter plate-based screening formats up to 1536-well plates with Z' factors of >0.75 and signal-to-noise ratios of >50. Using thioacylated lysine residues in p53-derived peptides, we optimized substrates for HDAC8 with a catalytic efficiency of >250000 M-1 s-1, which are more than 100-fold more effective than most of the known substrates. We determined inhibition constants of several inhibitors for human HDACs using thioacylated peptidic substrates and found good correlation with the values from the literature. On the other hand, we could introduce N-methylated, N-acylated lysine residues as inhibitors for HDACs with an IC50 value of 1 μM for an N-methylated, N-myristoylated peptide derivative and human HDAC11.
Keywords: Thioamides; biokatalýza; Histone Deacetylase Inhibitors; Histone Deacetylases; Lysine; thioamidy; lysin; lidé; Kinetics; histondeacetylasy; Biocatalysis; kinetika; inhibitory histondeacetylas; Humans